High temperature tribological behaviour of bonded surfaces based on the phase structure of the boride layer - Cimenoglu, Huseyin; Atar, Erdem; Motallebzadeh, Amir (Elsevier Science Sa, 2014)
This study focuses on the high temperature tribological behaviour of the boride layers generated on 4140 steel by pack bonding process. Bonding at 750 and 800 degrees C resulted in a single phase (Fe2B) boride layer, while a dual phase (Fe2B+FeB) boride layer was developed at 850 and 900 degrees C. Sliding wear tests conducted by rubbing an alumina ball revealed that single and dual-phase boride layers exhibited almost similar tribological performances and superior wear resistances at room temperature. With increasing testing temperature, boride layers exhibited different wear behaviours depending on their phase structure so that, dual phase boride layer yielded better wear resistance than single phase boride layer, especially at the testing temperature of 300 degrees C. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Diffusion treatments; High temperature; Sliding wear; Steel; Thermal effects; Wear testing